GOLD 2017 on the way to a phenotypic approach? Analysis from the Phenotypes of COPD in Central and Eastern Europe (POPE) Cohort. Issue 4 (27th April 2017) - Tudoric, Neven; Koblizek, Vladimir; Miravitlles, Marc; Valipour, Arschang; Milenkovic, Branislava; Barczyk, Adam; Somfay, Attila; Zykov, Kirill; Kostov, Kosta; Zbozinkova, Zuzana; Svoboda, Michal; Sorli, Jurij; et al.
Recently, the Global Initiative for Chronic Obstructive Lung Disease (GOLD) released a revised consensus report (2017 GOLD Report) [1] in which the formerly defined ABCD classification of patients with COPD has been refined. The 2011 GOLD Report and its 2016 Update classified patients on the basis of three variables, i.e. the symptom burden, lung function impairment and exacerbations [2], now the A–D groups are defined solely on the basis of symptoms and history of exacerbations – thus recognising the limitations of the forced expiratory volume in 1 s (FEV1 ) in influencing therapeutic decisions in COPD [1]. The obvious consequence of the new classification is a shift of a proportion of patients from the C to the A group, and from the D to the B group. Nevertheless, the magnitude of such redistribution remains unknown. The distribution of patients based on exacerbations solely is the most profound consequence of the 2017 GOLD Report http://ow.ly/4UJa309fLbM